2013
DOI: 10.3389/fpsyg.2013.00033
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Inverted Control in Measuring Holistic Face Processing with the Composite Effect and Part-Whole Effect

Abstract: Holistic coding for faces is shown in several illusions that demonstrate integration of the percept across the entire face. The illusions occur upright but, crucially, not inverted. Converting the illusions into experimental tasks that measure their strength – and thus index degree of holistic coding – is often considered straightforward yet in fact relies on a hidden assumption, namely that there is no contribution to the experimental measure from secondary cognitive factors. For the composite effect, a relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 110 publications
(169 reference statements)
1
54
0
1
Order By: Relevance
“…In contrast, other kinds of stimuli, such as buildings, objects, and pseudowords, are thought to be processed as a conjunction of individual parts (23,24). The same is true for faces that are inverted, negative contrast face images, and faces that have an unusual arrangement of parts (20,25). For stimuli that are not processed holistically, such as buildings and inverted faces, we propose that participants follow the typical strategy of deciding whether the item was on the study list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other kinds of stimuli, such as buildings, objects, and pseudowords, are thought to be processed as a conjunction of individual parts (23,24). The same is true for faces that are inverted, negative contrast face images, and faces that have an unusual arrangement of parts (20,25). For stimuli that are not processed holistically, such as buildings and inverted faces, we propose that participants follow the typical strategy of deciding whether the item was on the study list.…”
Section: Discussionmentioning
confidence: 99%
“…One difference between faces and other kinds of material is that faces are processed holistically (20)(21)(22), whereas buildings, objects, and pseudowords are not (23,24). Holistic processing of faces occurs only in the case of upright faces and not for inverted faces, negative contrast faces, or faces that have an unusual arrangement of features (20,25). With this in mind, we next tested recognition memory for inverted faces.…”
Section: Significancementioning
confidence: 99%
“…Similarly, the finding that composite interference is greatly diminished-although not eliminated entirely (e.g., Susilo, Rezlescu, & Duchaine, 2013)-when stimulus arrangements are shown upsidedown confirms that performance decrements in the uprightaligned condition are not induced by the presence of the continuous boundary when the halves are aligned; whereas the boundary is disrupted by misalignment, it is preserved by inversion (Rossion, 2013). Where effects of alignment are seen for upright, but not inverted arrangements, authors can also exclude the possibility that the differential interference observed in these conditions reflects differences in the size of the spotlight of visuospatial attention (e.g., McKone et al, 2013). For these reasons, many consider the use of convergent inverted and misaligned control conditions necessary for clear interpretation of composite interference (McKone et al, 2013;Rossion, 2013).…”
Section: Control Conditionsmentioning
confidence: 66%
“…Using the naming paradigm (A. W. Young et al, 1987), the authors found a comparable composite effect (i.e., greater composite interference in the aligned, than in the misaligned condition) in their clinical sample and matched controls, suggesting typical susceptibility to the illusion. However, in this particular investigation the authors utilized a misaligned control condition only; it is unclear whether the misalignment advantage is also seen for inverted composite arrangements (McKone et al, 2013).…”
Section: Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation